Definable group extensions and o-minimal group cohomology via spectral sequences (2013)
We provide the theoretical foundation for the Lyndon-Hochschild-Serre spectral sequence as a tool to study the group cohomology and with this the group extensions in the category of definable groups. We also present various results on definable modules and actions, definable extensions and group cohomology of definable groups. These have applications to the study of non-definably compact groups definable in o-minimal theories (see [1]).